1989
DOI: 10.1063/1.344470
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced forward transfer of high-T c YBaCuO and BiSrCaCuO superconducting thin films

Abstract: For the first time, the deposition of YBaCuO and BiSrCaCuO thin films has been performed by the single-laser pulse-induced forward transfer technique. In addition, the BiSrCaCuO films were successfully converted into the superconducting phase, with an onset critical temperature of about 90 K and a zero resistance at 80 K, by a subsequent thermal anneal in oxygen atmosphere in the 850–900 °C temperature range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(32 citation statements)
references
References 9 publications
0
30
0
2
Order By: Relevance
“…Under the action of the laser pulse, a tiny amount of the film material is transferred from the support to the flat substrate, which is placed parallel and at a short distance to the former one. Although LIFT was initially developed to deposit patterns of metals, 3 its use was quickly extended to other inorganic materials 4 and, more recently, to pastes and liquids. 5 The possibility of transferring liquids through LIFT revealed that this technique could be applied to the deposition of organic and biological materials in solution, since the liquid solvent would act simultaneously as energy absorber and transport vector of the molecules.…”
mentioning
confidence: 99%
“…Under the action of the laser pulse, a tiny amount of the film material is transferred from the support to the flat substrate, which is placed parallel and at a short distance to the former one. Although LIFT was initially developed to deposit patterns of metals, 3 its use was quickly extended to other inorganic materials 4 and, more recently, to pastes and liquids. 5 The possibility of transferring liquids through LIFT revealed that this technique could be applied to the deposition of organic and biological materials in solution, since the liquid solvent would act simultaneously as energy absorber and transport vector of the molecules.…”
mentioning
confidence: 99%
“…2 In recent years, significant study has been directed towards extending the range of materials that can be deposited using LIFT; metals, 3 oxides, 2 superconductors, 4 DNA, 5 proteins, 6 fungal spores, 7 polycrystalline Si, 8 and various important electronic and sensing materials 9 have all been transferred. In contrast, efforts to reduce the minimum achievable deposition dimensions have received comparatively little attention.…”
mentioning
confidence: 99%
“…Laser-induced forward transfer (commonly abbreviated to LIFT) is a direct-write technique that allows the selective transfer of many materials on a micrometer scale [1][2][3][4][5], including liquids [6] and living cells [7,8]. In the LIFT process, a thin film serves as a donor material that is to be transferred, which is referred to as the donor layer, see Fig.…”
Section: Introductionmentioning
confidence: 99%